2021
DOI: 10.1038/s41598-021-98454-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression reveals a molecular sexual identity of avian primordial germ cells at pre-gonadal stages

Abstract: In poultry, in vitro propagated primordial germ cells (PGCs) represent an important tool for the cryopreservation of avian genetic resources. However, several studies have highlighted sexual differences exhibited by PGCs during in vitro propagation, which may compromise their reproductive capacities. To understand this phenomenon, we compared the proteome of pregonadal migratory male (ZZ) and female (ZW) chicken PGCs propagated in vitro by quantitative proteomic analysis using a GeLC-MS/MS strategy. Many prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Alternatively, the lack of a relationship between α and generation times in birds could reflect their distinct germ cell development: Unlike mammals, avian sexual phenotype is directly determined by the sex chromosome content of individual cells [68, 69] and PGCs are determined by inheritance of maternally derived gene products [70]. Given these features, it seems plausible that sex differences in mutation rates appear earlier in onto-genesis in birds than in mammals, consistent with reported sex differences in the cellular phenotypes of PGCs prior to gonad development [71]. If indeed the developmental window when both sexes have a similar mutation rate is short in birds then, under our model, generation times are expected to have little to no influence on α .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Alternatively, the lack of a relationship between α and generation times in birds could reflect their distinct germ cell development: Unlike mammals, avian sexual phenotype is directly determined by the sex chromosome content of individual cells [68, 69] and PGCs are determined by inheritance of maternally derived gene products [70]. Given these features, it seems plausible that sex differences in mutation rates appear earlier in onto-genesis in birds than in mammals, consistent with reported sex differences in the cellular phenotypes of PGCs prior to gonad development [71]. If indeed the developmental window when both sexes have a similar mutation rate is short in birds then, under our model, generation times are expected to have little to no influence on α .…”
Section: Resultsmentioning
confidence: 83%
“…One possibility is that sex differences in mutation rates arise earlier in development: unlike in mammals, the avian sexual phenotype is directly determined by the sex chromosome content of individual cells [65, 66] and PGCs are determined by inheritance of maternally derived gene products (preformation) [67]. These features of germ cell development raise the possibility that sex-differences in mutation rates could appear earlier in ontogenesis in birds than in mammals, consistent with reported sex differences in the cellular phenotypes of PGCs prior to gonad development [68]. If the developmental window when both sexes have a similar mutation rate is indeed small, then assuming that the ratio of paternal-to-maternal mutation rate is roughly constant across parental ages, generation times should have no influence on α .…”
Section: Mainmentioning
confidence: 81%
“…Although the PGC precursor cells transplanted into chicken embryos of the opposite sex at the blastodermal stage could differentiate into functional gametes 10 , circulating PGCs (cPGCs) transplanted into the bloodstream barely differentiate into functional gametes 11 , 12 . Additionally, the number of PGCs located in the intermediate mesoderm and the capacity of cultured PGCs derived from embryonic blood to uptake proteins differ between males and females 13 , 14 . Although a recent study showed that donor PGC-derived offspring could be produced using genetically infertile chickens of the opposite sex as recipients 15 , the sex determination mechanism of PGCs remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Avian PGCs have characteristic developmental features, such as migration into the gonads using the vascular system [ 2 ]. Chicken PGCs have also shown a unique sex determination mechanism in which PGC-intrinsic factors may occur in a cell-autonomous manner [ 3 , 4 , 5 ]. In addition, several studies have revealed the self-renewal mechanism of chicken PGCs, resulting in the establishment of stable culture protocols for chicken PGCs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%